2017
DOI: 10.26417/ejms.v4i3.p24-32
|View full text |Cite
|
Sign up to set email alerts
|

SMEs’ Intention towards Sustainable Entrepreneurship

Abstract: Environmental degradation could be considered as one of the negative consequences of entrepreneurial activities. As such, entrepreneurs are urged to be proactive in resolving environmental problems through sustainable entrepreneurship. However, this new practice has not been fully accepted and exercised by many SMEs. Moreover, the studies pertaining to sustainable entrepreneurship are also very scarce in the literature. Therefore, this paper was conducted to investigate the contexts that directly and indirectl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…The definition of sustainability is the general agreement to retain a balance between economic, environmental, and social factors on an equal and harmonious basis to meet current needs without affecting the needs of future generations [19]. According to reports of the World Commission on Environment Development (WCED) (initially in 1934), in 1987 [20,21], Schumpeter elaborated on the innovation process of creative destruction [7,22,23], whether it be climate change, biodiversity, or water shortages, in which entrepreneurs are constantly innovating based on environmental challenges. These degradations have indeed become a fuse for the entrepreneurial creativity of the future.…”
Section: Sustainability Concerns and Sustainable Entrepreneurship In Agriculturementioning
confidence: 99%
See 2 more Smart Citations
“…The definition of sustainability is the general agreement to retain a balance between economic, environmental, and social factors on an equal and harmonious basis to meet current needs without affecting the needs of future generations [19]. According to reports of the World Commission on Environment Development (WCED) (initially in 1934), in 1987 [20,21], Schumpeter elaborated on the innovation process of creative destruction [7,22,23], whether it be climate change, biodiversity, or water shortages, in which entrepreneurs are constantly innovating based on environmental challenges. These degradations have indeed become a fuse for the entrepreneurial creativity of the future.…”
Section: Sustainability Concerns and Sustainable Entrepreneurship In Agriculturementioning
confidence: 99%
“…As sustainable entrepreneurship studies have progressed [6,20,23,[32][33][34][35][36] and as research continues to deepen, sustainable entrepreneurship has become a synergistic combination of entrepreneurial programs and sustainable development. Consideration of the principles of sustainable development leads to the use of natural resources that reflects the balance between profit, social goals, and ecological goals.…”
Section: Sustainability Concerns and Sustainable Entrepreneurship In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…Social sustainability involves the ability of entrepreneurs to be answerable to different stakeholders such as the community, workers, suppliers, customers as well as the government voluntarily (Lu and Taylor, 2016;Majid et al, 2017;Moshina, 2015;Nevia, 2015). The social dimension of sustainable entrepreneurship requires university students to fulfil their responsibilities towards the stakeholders and the social setting in which they intend to operate as they undertake entrepreneurial actions (Ciasullo and Troisi, 2013).…”
Section: Sustainable Entrepreneurshipmentioning
confidence: 99%
“…Previous studies indicate several determinants of sustainability intention for example, Koe and Majid (2014) revealed that socio-cultural factors such as time orientation, sustainability orientation and social norm significantly influence sustainability intention. In addition, Majid et al (2017) reported that positive sustainable value, favourable sustainable attitude, supporting social norms, and sufficient government legislation positively affect sustainability intention of entrepreneurs. Bădulescu et al (2014) further revealed that business students have a positive attitude towards sustainability intention.…”
Section: Introductionmentioning
confidence: 99%